Molecular evidence for adaptive evolution of drought tolerance in wild cereals. Issue 2 (29th November 2022) - Wang, Yuanyuan; Chen, Guang; Zeng, Fanrong; Han, Zhigang; Qiu, Cheng‐Wei; Zeng, Meng; Yang, Zujun; Xu, Fei; Wu, Dezhi; Deng, Fenglin; Xu, Shengchun; Chater, Caspar; et al.
Summary: The considerable drought tolerance of wild cereal crop progenitors has diminished during domestication in the pursuit of higher productivity. Regaining this trait in cereal crops is essential for global food security but requires novel genetic insight. Here, we assessed the molecular evidence for natural variation of drought tolerance in wild barley ( Hordeum spontaneum ), wild emmer wheat ( Triticum dicoccoides ), and Brachypodium species collected from dry and moist habitats at Evolution Canyon, Israel (ECI). We report that prevailing moist vs dry conditions have differentially shaped the stomatal and photosynthetic traits of these wild cereals in their respective habitats. We present the genomic and transcriptomic evidence accounting for differences, including co‐expression gene modules, correlated with physiological traits, and selective sweeps, driven by the xeric site conditions on the African Slope (AS) at ECI. Co‐expression gene module 'circadian rhythm' was linked to significant drought‐induced delay in flowering time in Brachypodium stacei genotypes. African Slope‐specific differentially expressed genes are important in barley drought tolerance, verified by silencing Disease‐Related Nonspecific Lipid Transfer 1 ( DRN1 ), Nonphotochemical Quenching 4 ( NPQ4 ), and Brassinosteroid‐Responsive Ring‐H1 ( BRH1 ). Our results provide new genetic information for the breeding of resilient wheat and barley in a changing global climate with increasingly frequent drought events.